Anticipative marketing as an entrance to achieve customer value: A Case Study to the opinions of a worker’s sample in the Carrefour Dohuk store - Salih, Sami (Humanities Journal of University of Zakho, 2022)
The current research studies anticipative marketing as an entrance to achieving customer value, and the researcher has prepared a theoretical side by adopting the theoretical literature of the subject, and in order to reach an answer to the question (Is anticipative marketing a relationship and a moral effect to achieve customer value?) A model was assumed, and to clarify the nature of the relationship and the impact between the research variables represented By anticipative marketing (the independent variable) and the value of the customer (the dependent variable), in the light of which two main hypotheses were built, one for the relationship and the other for influence, from which five hypotheses are branched, and by distributing the questionnaire to a sample of individuals working in the Carrefour Dohuk store, the data required for Practical research, and using a set of statistical methods and programs, the collected data were analyzed and tested. And their desires precisely, to develop and present products in ways that meet the needs and desires in a way that is consistent with or even exceeds the expectations of customers, was one of the most important research proposals.